2010
DOI: 10.2147/opth.s14521
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of two methods of screening for diabetic retinopathy by nonmydriatic fundus camera

Abstract: Purpose:To compare the results obtained by two screening techniques for diabetic retinopathy.Methods:Patients were assessed in two groups, according to whether the retinal images were analyzed by the general practitioner (Group 1) or by the ophthalmologist (Group 2) in a two-year prospective study using telemedicine.Results:The number of patients referred to the nonmydriatic fundus camera unit was higher in Group 1 than in Group 2 (63.80% versus 17.63%). Greater patient adherence was observed in Group 1 than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Diabetic retinopathy is the most common microvascular complication of diabetes (Antonetti et al, 2012), and after two decades of diabetes, almost all T1D patients will have some degree of retinopathy, as will more than 80% of insulin-treated T2D patients and 50% of those not requiring insulin (Klein et al, 1989;Romero-Aroca et al, 2010).…”
Section: The Global Significance Of Diabetic Retinopathymentioning
confidence: 99%
“…Diabetic retinopathy is the most common microvascular complication of diabetes (Antonetti et al, 2012), and after two decades of diabetes, almost all T1D patients will have some degree of retinopathy, as will more than 80% of insulin-treated T2D patients and 50% of those not requiring insulin (Klein et al, 1989;Romero-Aroca et al, 2010).…”
Section: The Global Significance Of Diabetic Retinopathymentioning
confidence: 99%
“…At present, the number of patients with diabetes has reached 90 million in China 2 . After 20 years of diabetes, nearly all patients with type I diabetes, 80% of patients with type 2 diabetes requiring insulin treatment and 50% of those not requiring insulin treatment exhibit some degree of DR 3 .…”
mentioning
confidence: 99%
“…Currently, there is a lack of evidence on screening specifically for DME; however, detection of DME is important because this condition is the leading cause of blindness in patients with type 2 diabetes [97]. One study from a DME screening program in Hong Kong demonstrated a high false positive rate (86.6%) and a low positive predictive value (13.4%) for screening of DME with mydriatic FP, if macular thickness was used to define the presence of macular edema [98].…”
Section: Screening For Dmementioning
confidence: 99%